Senktide, a selective neurokinin B-like agonist, elicits serotonin-mediated behaviour following intracisternal administration in the mouse. - Stoessl, A; Dourish, C; Young, S; Williams, B; Iversen, S; Iversen, L (1987)
Behavioural responses to tachykinins were observed following intracisternal administration in mice. The synthetic NK-3 agonists senktide and L-363,851 caused behaviour typically associated with serotonergic stimulation, including head twitches, reciprocal forepaw treading and hindlimb splaying. Neurokinin B produced some features of the serotonin (5-HT) syndrome, while substance P, neurokinin A and eledoisin failed to elicit any such behaviours. Senktide-induced head twitches were prevented by pretreatment with the 5-HT2 antagonists ketanserin and ritanserin, while forepaw treading was attenuated by the 5-HT1 antagonists (-)-pindolol and methysergide. These data suggest that NK-3 agonists interact with central 5-HT mechanisms.